OPPORTUNITIES AND PROSPECTS OF USE OF OLFACTORY METHOD IN CRIMINALISTICS AND FORENSICS - T. F. Moiseeva (Теория и практика судебной экспертизы)
Discusses the history of the formation of the forensic human odor traces and basic principles on the use of olfactory method in expert research. Analyzed opportunities and future directions olfactory research in criminalistics and the forensic examination.